Optical Multi-Tap RF Canceller for In-Band Full-Duplex Wireless Communication Systems - Yunlu Xing; Shangyuan Li; Xiaoxue Chen; Xiaoxiao Xue; Xiaoping Zheng (IEEE Photonics Journal, 2022)
In-band full-duplex (IBFD) technology has become important for future wireless communications, due to its ability of increasing the radio-frequency (RF) spectrum efficiency. However, the benefits can only be realized if the self-interference (SI) is sufficiently suppressed. RF cancellation is important for IBFD systems due to its ability of SI mitigation. But it becomes more difficult for RF cancellation while the frequency and bandwidth increase. In real scenarios, the response of the multi-path SI channel is not frequency-flat, which also limits the cancellation performance. To solve these problems, we present a photonic-enabled multi-tap RF canceller in this paper. The proposed RF canceller has the ability of cancelling multi-path SI. The tap coefficients are precisely adjusted by optical spectrum processing. A prototype system with 8 taps is demonstrated in this paper. The measured results show 25 dB average cancellation depth over 1 GHz cancellation bandwidth under over-the-air conditions. To verify the signal of interest (SOI) recovery capability of the novel RF canceller, an IBFD wireless communication experiment based on 16-quadrature amplitude modulation (16-QAM) was demonstrated, the SOI was successfully recovered.